TRADISI, TRANSFORMASI DAN MASA DEPAN PEMIKIRAN ISLAM DI INDONESIA DALAM PERSPEKTIF SOSIOLOGIS - Arifin, Syamsul (Jurnal Bestari, 1994)
Islamic thought is a dynamic aspect of the Islamic obsevers to conduct examinations based on various interdisciplinary approaches. As a dynamic aspect, the Islamic thought experiences the process of reformation and transformation in its form which is in contemporary pattern. Altough it always develops, caused by its creative and dynamic dialect between "the big tradition" (Islam) and "the small one" the Islamic thought often shows its wholeness since it stands on Islamic doctrine which is universal. By using sociological approach, this article describes again the development of the Islamic thought.